Pemanfaatan Aplikasi E-Scan Sebagai Digitalisasi Layanan Administrasi Persuratan Mahasiswa - Nursahwal, Nursahwal; Domopolii, Muljono; Mardhiah, Mardhiah (Jurnal Manajemen dan Budaya, 2025)
This study examines the use of the e-Scene application in administrative correspondence services. This application is a digital innovation that aims to speed up processes, simplify access, and increase transparency in the delivery of academic documents. The research method used is descriptive qualitative with data collection techniques through interviews and documentation. Respondents in this study were students who actively use the e-Scene application in managing correspondence services. The data analysis technique used in this study is descriptive analysis through data reduction, data presentation, and drawing conclusions. Meanwhile, data validity testing was carried out by triangulation methods by comparing information or data through various means, namely from interviews, documentation, and direct observation. The results of the study show that students gave a positive response to the use of e-Scene because it is considered efficient, easy to use, and provides real-time information on letter status. This application also runs stably on various devices without significant technical problems. Students proposed additional features in the form of automatic notifications and a reminder system to speed up responses from related parties. These findings indicate that the success of a digital system is not only determined by technology, but also by leadership and user participation.